Desenvolvimento de compósito de blenda polimérica a partir de descartes do processo de fabricação de revestimento interno automotivo - Fujii, Laura Caldini [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In 2020, plastic waste represented 16,8% off all the Urban Solid Waste (USW) created and a large part of this waste is incorrectly disposed, generating numerous environmental impacts. The use of polymers in the automotive industry has been growing significantly, due to several benefits such as cost reduction, weight loss, performance improvement, among others. The recycling of these materials is a major challenge nowadays, since most polymers parts are used together, and they are joined by chemical adhesives due to their lack of good compatibility. This characteristic prevents the recycling and makes separation unfeasible, where they must be disposed as a single waste. The present research aims to analyze the polymeric residues present in the automotive interior coating scraps generated by an auto parts industry, in order to understand their possible interactions through the formation of a polymer blend composite (glass fiber, polyester fiber and polyurethane) in the shape of a plate. In addition, it develops possible ways to reuse this material, thus obtaining a product with both economic advantages, by turning waste into a marketable material, and with environmental advantages, reducing the amount of waste sent to the landfill monthly and reducing the demand for virgin raw materials. To achieve the objectives, the materials present in the waste were analyzed by differential scanning calorimetry to assist in the blend consolidation strategy, later a plate was projected with the overlap of layers using a hot press. The composites formed were evaluated by three-point bending test and their structure was analyzed using scanning electron microscopy. The good result in flexural properties indicates a good consolidation tactics when compared with results in literature, what is explained by the presence of glass fiver and PET in the blend composition. Through the SEM images, it was possible to observe a good interface between the glass fiber and the polyester-based polymer matrix of the wastes, directly influencing the mechanical results of the material.

No ano de 2020, o resíduo plástico representou 16,8% de todo resíduo sólido urbano (RSU) gerado, além disso grande parte desses resíduos são descartados de maneira incorreta, gerando inúmeros impactos ambientais. A utilização de polímeros na indústria automotiva vem crescendo significativamente, devido aos diversos benefícios como redução de custos, diminuição de peso, melhoria de desempenho, entre outros. A reciclagem desses materiais é um grande desafio atualmente, já que em grande parte das peças os polímeros são utilizados em conjunto, e são unidos por adesivos químicos por não apresentarem boa compatibilidade. Tal característica impede a sua reciclagem e inviabiliza a separação, devendo ser destinados como um único resíduo. A presente pesquisa visa analisar os resíduos poliméricos presentes nas aparas de revestimento interno automotivo geradas por uma indústria de autopeças, a fim de entender suas possíveis interações por meio da formação de um compósito de blenda polimérica (fibra de vidro, fibra de poliéster e poliuretana) em forma de placa. Além disso, desenvolver possíveis formas de reutilizar esse material, obtendo, assim, um produto tanto com vantagens econômicas, por tornar um resíduo em um material comercializável com vantagens ambientais, reduzindo a quantidade de resíduos enviados mensalmente para o aterro sanitário e reduzindo a demanda por matérias primas virgens. Para atingir os objetivos, os materiais presentes na apara foram analisados por calorimetria exploratória diferencial de forma a auxiliar na estratégia de consolidação da blenda, posteriormente foi gerada uma placa com a sobreposição de camadas utilizando uma prensa à quente. Os compósitos formados foram avaliados por flexão de três pontos e sua estruturada foi analisada a partir da microscopia eletrônica de varredura. Os bons resultados nas propriedades em flexão indicaram boa estratégia de consolidação quando comparado com resultados da literatura, explicado pela a presença da fibra de vidro e do PET na composição da blenda. Através das imagens de MEV foi possível observar boa interface entre a fibra de vidro e a matriz polimérica a base de poliéster das aparas, influenciando diretamente nos resultados mecânicos do material.
Development of polymeric blend composite from internal auto parts waste
Keywords: Mechanical recycling; Manufacturing additives; Mechanical properties; Fractography; Interfacial bonding; Reciclagem mecânica; Compatibilizante; Propriedades mecânicas; Fractografia; Ligação interfacial